Virtual Pharmacophore Screening Identifies Small‐Molecule Inhibitors of the Rev1‐CT/RIR Protein–Protein Interaction. (21st August 2019) - Dash, Radha C.; Ozen, Zuleyha; McCarthy, Kaitlyn R.; Chatterjee, Nimrat; Harris, Cynthia A.; Rizzo, Alessandro A.; Walker, Graham C.; Korzhnev, Dmitry M.; Hadden, M. Kyle
Abstract: Translesion synthesis (TLS) has emerged as a mechanism through which several forms of cancer develop acquired resistance to first‐line genotoxic chemotherapies by allowing replication to continue in the presence of damaged DNA. Small molecules that inhibit TLS hold promise as a novel class of anticancer agents that can serve to enhance the efficacy of these front‐line therapies. We previously used a structure‐based rational design approach to identify the phenazopyridine scaffold as an inhibitor of TLS that functions by disrupting the protein–protein interaction (PPI) between the C‐terminal domain of the TLS DNA polymerase Rev1 (Rev1‐CT) and the Rev1 interacting regions (RIR) of other TLS DNA polymerases. To continue the identification of small molecules that disrupt the Rev1‐CT/RIR PPI, we generated a pharmacophore model based on the phenazopyridine scaffold and used it in a structure‐based virtual screen. In vitro analysis of promising hits identified several new chemotypes with the ability to disrupt this key TLS PPI. In addition, several of these compounds were found to enhance the efficacy of cisplatin in cultured cells, highlighting their anti‐TLS potential. Abstract : Lost in translesion : We used a pharmacophore‐based virtual screen to identify novel small‐molecule scaffolds that disrupt the protein–protein interaction (PPI) between the C‐terminal domain of Rev1 and the Rev1 interacting region present in multiple translesion synthesis (TLS) polymerases. This PPI is essential for the proper function of TLS, and its disruption demonstrates promise as an anticancer therapeutic target.